2022
DOI: 10.1088/1742-5468/ac72a1
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement Hamiltonian during a domain wall melting in the free Fermi chain

Abstract: We study the unitary time evolution of the entanglement Hamiltonian of a free Fermi lattice gas in one dimension initially prepared in a domain wall configuration. To this aim, we exploit the recent development of quantum fluctuating hydrodynamics. Our findings for the entanglement Hamiltonian are based on the effective field theory description of the domain wall melting and are expected to exactly describe the Euler scaling limit of the lattice gas. However, such field theoretical results can be recovered fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 112 publications
2
15
0
Order By: Relevance
“…Interchanging j → −j, one clearly arrives at the same definition of the weights as in (29) for the double interval. Hence, in the limit N → ∞, one has S(x i ) → 2π β (x) as well as C(x i ) → 0, perfectly reproducing the result (37) and (38) for the boundary Dirac theory with α = 0, π. The case 0 < α < π can also be studied on the lattice by introducing a chemical potential at the first site, i.e.…”
Section: J Stat Mech (2022) 083101supporting
confidence: 77%
See 2 more Smart Citations
“…Interchanging j → −j, one clearly arrives at the same definition of the weights as in (29) for the double interval. Hence, in the limit N → ∞, one has S(x i ) → 2π β (x) as well as C(x i ) → 0, perfectly reproducing the result (37) and (38) for the boundary Dirac theory with α = 0, π. The case 0 < α < π can also be studied on the lattice by introducing a chemical potential at the first site, i.e.…”
Section: J Stat Mech (2022) 083101supporting
confidence: 77%
“…For slowly varying inhomogeneities, the continuum entanglement Hamiltonian for a single interval can be obtained [36] via the curved-space CFT approach [37]. Recently it has been shown that the continuum limit can be generalized to recover the local terms for the domainwall melting problem [38]. It would be interesting to check whether this treatment could be extended to the bi-local terms in case of two intervals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, various inhomogeneous generalisations of (1) were studied in connection to inhomogeneous and time-dependent problems in TLLs, both in- [7][8][9][10][11][12][13] and out-of-equilibrium [8,[14][15][16][17][18][19][20][21][22][23][24], mainly aiming at describing gases in traps and their non-equilibrium dynamics (see Section V in Ref. [25] for a more comprehensive review of the literature).…”
Section: Introductionmentioning
confidence: 99%
“…In this manuscript, we prepare an initial state with a domain wall localised at the defect and we let it melt. Without the defect, this is a protocol that has been studied intensively in the free fermionic literature [32][33][34][35][36][37][38][39][40][41][42][43][44][45] and it represents a case study for the application of hydrodynamics to non-equilibrium quantum systems (recently adapted also to interacting integrable models [46,47] with the generalised hydrodynamics formalism [48,49]). Anyhow, the presence of the defect is expected to alter dramatically the evolution at a qualitative level.…”
mentioning
confidence: 99%